Depression in Heart Failure: Psychosomatic Approachv - Putranto, Rudi; Shatri, Hamzah; Wijaya, Ika Prasetya; Faisal, Edward (Jurnal Penyakit Dalam Indonesia, 2021)
Depression is a common condition in heart failure (HF) and is considered a risk factor for cardiovascular disease. Depression disorder in patients with heart disease paradigmatically defines a psychosomatic-somatopsychic challenge to any health delivery. However, despite the devastating effects of depression, it is often underdiagnosed and receives little attention in heart failure patients. This review provides an extensive overview of HF regarding epidemiology, disease pathophysiology, diagnosis, and management from the latest literature. Based on the literature review, the prevalence of depression in heart failure in Indonesian patients was 5.3-42%. Psychological stress experienced by people suffering from depression can cause dysregulation in the sympathetic nervous system and hypothalamic–pituitary–adrenal (HPA) axis. This mechanism, in turn, has some deleterious downstream effects, including the development of hypertension, left ventricular hypertrophy, coronary vasoconstriction, endothelial dysfunction, platelet activation, and the production of pro-inflammatory cytokines. The Diagnostic and Statistical Manual of Mental Disorders-5 (DSM-5), published by the American Psychiatric Association, is used to diagnose depression in patients with HF. Meanwhile, the Patient Health Questionnaire (PHQ)-2 and PHQ-9 are commonly used as screening tools for depression in patients with HF. The Biopsychosocial-spiritual model as a psychosomatic approach have might reduce or prevent depression and thus improve quality of life and other outcomes. Evidence reveals that both psychotherapeutic treatment (e.g., cognitivebehavioral therapy) and pharmacologic treatment (e.g., use of the selective serotonin reuptake inhibitor sertraline) are safe and effective in managing depression in patients with cardiovascular disease. In conclusion, the review of articles in this paper shows that there is a high prevalence of depression in heart failure, but it is often not recognized by doctors, there is a relationship between psychosomatic, and heart failure, non-pharmacological interventions such as psychotherapy and pharmacological therapy have benefits. Future research is needed to create evidence-based evaluations and treatment algorithms tailored to the specific needs of the target population.